2014
DOI: 10.1097/01.tp.0000442774.46133.71
|View full text |Cite
|
Sign up to set email alerts
|

15-Year Follow-up of a Multicenter, Randomized, Calcineurin Inhibitor Withdrawal Study in Kidney Transplantation

Abstract: Fifteen years after conversion to a CNI free regimen, there was no benefit regarding graft and patient survival or regarding prevalence of or death by comorbidities. However, rejection shortly after CNI withdrawal was associated with decreased graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Steroids have multiple adverse effects, such as increased risk of infection, hyperglycemia, accelerated atherosclerosis, and gastrointestinal bleeding, while calcineurin inhibitors are associated with neurotoxicity and nephrotoxicity, as well as risk of infection and an increased risk of cancer (Arnold et al, 2013; Crutchlow and Bloom, 2007; Guba et al, 2004; Hoorn et al, 2012; Roodnat et al, 2014). In this regard, we propose that our anti-metabolic regimen has certain advantages over conventional treatments in terms of avoiding some of these side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids have multiple adverse effects, such as increased risk of infection, hyperglycemia, accelerated atherosclerosis, and gastrointestinal bleeding, while calcineurin inhibitors are associated with neurotoxicity and nephrotoxicity, as well as risk of infection and an increased risk of cancer (Arnold et al, 2013; Crutchlow and Bloom, 2007; Guba et al, 2004; Hoorn et al, 2012; Roodnat et al, 2014). In this regard, we propose that our anti-metabolic regimen has certain advantages over conventional treatments in terms of avoiding some of these side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term use of immunosuppressants results in a broad range of co-morbidity. For example, calcineurin inhibitors are associated with hyperlipidemia, hyperglycemia, neuro- and nephro-toxicity, as well as an increased risk of malignancy (Arnold et al, 2013; Crutchlow and Bloom, 2007; Guba et al, 2004; Hoorn et al, 2012; Roodnat et al, 2014). In addition, such agents inhibit negative regulatory and tolerance-inducing responses (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary end points (6,12,18, and 24 months) included incidence of AR, eGFR, 28 allograft and subject survival rates, and percentage of subjects with de novo post-transplant DSA.…”
Section: Clinical End Pointsmentioning
confidence: 99%
“…4,5 The adverse effects of CNIs, including drug-induced renal parenchymal fibrosis, allograft dysfunction, and cardiovascular morbidity among others, have raised concerns that CNIs may contribute to poor long-term outcomes and have resulted in a desire to develop immunosuppression protocols that avoid, withdraw, or minimize their use. [6][7][8] Published studies of CNI withdrawal in unselected cohorts of kidney transplant recipients taking standard three-drug immunosuppression indicate that elimination of CNI increases the risk of AR, 6,7,[9][10][11][12][13][14][15][16] which can potentially precipitate a fibrogenic process that contributes to graft failure. Some of these previous trials targeted patients who are apparently low risk as defined by relatively limited conventional clinical criteria, including living donor source, human leukocyte antigen (HLA) matching (particularly at class II loci), and lack of HLA sensitization.…”
mentioning
confidence: 99%
“…It thus remains to be seen whether belatacept will replace Tac as the first-line immunosuppressive drug anytime soon [13][14][15]. Multicenter, randomized clinical studies also showed higher incidences of acute rejection and dnDSA development in the Tac withdrawal or rapamycin-based groups compared with Tac-based regimen [1,3,16,17] In the foreseeable future, no other novel immunosuppressants are likely to emerge that can replace Tac.…”
Section: Introductionmentioning
confidence: 99%